THE SUPPLY SIDE FACTORS IMPACT ON THE EFFECTIVENESS OF INDONESIAN GOVERNMENT INTERNAL AUDIT FUNCTION - Alwi, Bramastya Datum; Yuyetta, Etna Nur Afri (Riset Akuntansi dan Keuangan Indonesia, 2020)
This study examines the effect of supply-side variables on the effectiveness of the Government Internal Supervisory Apparatus (GISA) function. These variables are organizational competence, organizational independence, compliance with audit implementation standards, risk-based audit planning, implementation of the Quality Assurance and Improvement Program (QAIP) and auditee attributes. The samples used in this study were 81 GISA units at the level of district and city governments. This work used a questionnaire to measure variables. Each unit of GISA was represented by a structural official or supervisor/auditor. Personnel occupying these positions were selected because they are considered to have an adequate understanding of the GISA. This study provides empirical evidence that, in the context of the Indonesian Government, organizational competence, risk-based audit planning and implementation of QAIP do not have a significant positive effect on the effectiveness of GISA’s function. Meanwhile, organizational independence, compliance with audit implementation standards and auditee attributes have a significant positive effect on the effectiveness of GISA’s function.